Identification and Analysis of Factors Influencing the Development of Research Competencies among Faculty Members in Iraqi Universities - Al-Gburi, Luay Jubair Hussein; Shahidi, Nima; Ahmed, Qusai Shihab; Rahmani, Jahanbakhsh (Assessment and Practice in Educational Sciences, 2026)
The purpose of this study was to identify and analyze the components influencing the development of research competencies among faculty members in Iraqi universities. This applied research was conducted using a descriptive–analytical approach, and data were collected through a researcher-made questionnaire administered to 333 faculty members. To analyze the data and rank the components, the Friedman test was employed to determine the priority and relative importance of each component across six main categories: causal factors, research competencies, contextual conditions, intervening conditions, strategies, and outcomes. The findings indicated that among the causal factors, professional requirements and motivational factors held the greatest importance and played a key role in shaping the research behavior of faculty members. Within the research competency components, research ethics and methodological knowledge were of higher significance, emphasizing adherence to ethical principles and mastery of scientific methods as fundamental pillars of research capability. Furthermore, within the contextual conditions, the scientific–educational environment had the highest importance, underscoring the vital role of research infrastructure and resources in enhancing the quality of scholarly activities. Among the intervening conditions, organizational barriers were identified as the main impediment, while within the strategy components, educational and motivational strategies had the most substantial effect on improving research competency. Finally, the individual outcomes for researchers were highly significant, demonstrating that the development of research competencies not only enhances professional performance but also increases motivation, self-confidence, and the ability to supervise students effectively. The results of this study highlight the necessity of a comprehensive and multidimensional approach to research empowerment among faculty members and can serve as a practical framework for planning, enhancing research competencies, and evaluating research performance in Iraqi universities.